2013
DOI: 10.1123/ijspp.8.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Change-of-Direction Movements in Young Rugby Players

Abstract: The evaluation of change-of-direction (COD) performance is strongly focused on the time spent to perform the test trials, while much less is known about the technical execution adopted during the COD movements. Thus, the purposes of this study were to evaluate (1) the relationship between straight- and COD-sprint tests and (2) the technical execution of COD movements in relation to different age categories of young rugby players. Young rugby players (N = 157, age range 8–19 y) completed a test battery composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 17 publications
5
35
0
Order By: Relevance
“…The analysis of relationships between straight and change-of-direction sprint tests added new evidence to the understanding of speed and agility performance. As already demonstrated in adult and young rugby players 3,4 and young basketball players, 5 college football athletes showed a significant relationship (r = .86, P < .0001) between straight sprint and sprint with changes of direction, sharing 74% of common variance. Furthermore, this relationship is supported by the idea of Young et al, 6 who argued that the greater the change-of-direction angle the less the skills have in common.…”
Section: Discussionsupporting
confidence: 66%
“…The analysis of relationships between straight and change-of-direction sprint tests added new evidence to the understanding of speed and agility performance. As already demonstrated in adult and young rugby players 3,4 and young basketball players, 5 college football athletes showed a significant relationship (r = .86, P < .0001) between straight sprint and sprint with changes of direction, sharing 74% of common variance. Furthermore, this relationship is supported by the idea of Young et al, 6 who argued that the greater the change-of-direction angle the less the skills have in common.…”
Section: Discussionsupporting
confidence: 66%
“…Agility motor tasks could be reactive or programmed [7]. Scientific literature reported that training programmes that use COD patterns assisted in the improvement of straight sprint performance, the COD ability and the muscular power and strength development [8]. However, many other studies have indicated that the COD training method did not improve these physical qualities [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…These results are confirmed by studies of Taskin, & Bicer (2015), Thakur, Mishra, & Rathore (2016) and Çñmenlñ, Koç, Çñmenlñ, & Kaçoğlu (2016), to develop appropriate training techniques for athletes. In addition, the level of development of explosive speed, speed endurance and strength affects on the intensity of the game activity of rugby players (Condello, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%